Accelerated leadership development in emerging economies - Korotov, Konstantin (Henry Stewart Talks, 2014)
Demand for talent in emerging markets, Strategies for attracting and retaining talent, Leadership development programs fail rather often, Differences in perceived challenges of managers, What keeps leadership talent awake at night, Compare with concerns of emerging economies, Appropriateness of traditional leadership methods, Classroom training, Distance learning/e-learning, Experiential leadership exercises, Mentoring, Professional coaching, Peer coaching, Global assignments in distributed teams, Leadership development professionals